New Sunday Times, 26 April 2009 - Intan Maizura Ahmad Kamal (The New Straits Times Press (M) Bhd, 2009)
Girls, size does not matter! at least not when it comes to choosing your diamonds, says Brian McHardy, a master diamond cutter from South Africa flown in especially by Habib Jewels for their month long annual Diamond Fest. In town to show the art of diamond cutting, McHardy also unveiled the spectacular new diamond collection by Hearts on Fire that pays homege to eight of the world's most inspiring architectural feats.